Aplikasi Pelayanan Administrasi Berbasis Website Pada Puskesmas Rawat Inap Hantakan - Jannah, Annisa; Hamid, Abdul; Naury, Chairullah (Politeknik Harapan Bangsa Surakarta, 2024)
The Hantakan Inpatient Health Center requires a website-based administrative service application to help simplify administrative processes and provide more effective services. The purpose of this study was to design and develop an effective and efficient website-based administrative service application for the Hantakan Inpatient Health Center. Data collection methods used in this research are observation, interviews, and literature study. This study uses the System Development Life Cycle (SDLC) approach with the Waterfall model. The result of this study is a website-based application that is integrated with the administration system of the Hantakan Inpatient Health Center, which makes it easier for patients to register, make appointments, and arrange doctors' schedules. In addition, this application also provides information about the types of services and facilities available at the Hantakan Inpatient Health Center. It is hoped that this application can increase the effectiveness and efficiency of administrative services at the Hantakan Inpatient Health Center.